Work ethics through the lens of American and British linguocultures: dominant cultural values - Ivanova S.V. (Язык и текст, 2016)
The article throws light on the peculiarities language consciousness functions and the way it reflects values of a certain linguocultural community. In particular, the article reveals the specificity of the verbalization of work ethics in American and British linguocultures. The language material testifies to deeply rooted discrepancies in the evaluative worldview of the cultures under study. If American culture considers work ethics as an indispensable part of a person’s life, the attitude to work in British culture is more complicated and ambiguous.